Regarding the mathematical character ”“ or not ”“ of the Eudemian Ethics method - Gazoni, Fernando Maciel (Revista Archai, 2017)
Joseph Karbowski (Karbowski, 2015) recently proposed to reevaluate Allan's claim of considering the method of the Eudemian Ethics as ‘quasi mathematical’ (Allan, 1961). In this paper I argue that the dispute about the method in the Eudemian treatise would be more perspicuously done if, instead of searching for or denying mathematical features in the Eudemian Ethics, we strive to analyze the linguistic features of verbs using for introducing the premisses in the Eudemian treatise as well as in other texts as the Euclidean Elements. Besides, be it mathematical or not, the interpretations proposed by Allan and Karbowski are not capable of providing a full explanation of some important differences between books I and II of the Eudemian Ethics, differences for which I propose some tentative answers.